(3GdQjGV GdRGgQI aj fXe CQHGH GdUaGJ GdaGNQIs - (3eMeO Hf YHO Gddg Hf eMeO, GdYjOQhS,J (B1005 (3g` s ((3YHO GdQMef GdHGQ s)
(3ChdgG (B:s
(3jbhd QGLi GdYah ef QH GdSeG hGdchf ai Sdc cQGe MceG GdHGQ ef jDgd GdEMSGfG aVdG ef GdefGf hGeJfGfG s
(3BNQgG (B:s
(3hGdMeO ddg Ydi EMSGfg haVdg GdeHShW hEeJfGfg hGdfXe gPG bO JfGgi fbdg JGQjNg aJM hNjQ LYdg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B252 - (3U(B259s
(3GdfSNI HgG MhGTs
(3efXheIs
(3Ydi ghGeTgG JbjjOGJs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs